2016
DOI: 10.1016/j.ipej.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictors and outcomes of hematoma after ICD implantation: An analysis of a nationwide database of 85,276 patients

Abstract: BackgroundPocket hematoma is one of the most common complications following cardiac device implantation. This study examined the impact of this complication on in-hospital outcomes following Implantable Cardioverter Defibrillator (ICD) implantation.MethodsData from Nationwide Inpatient Sample (NIS) 2010 was queried to identify all primary implantations of ICDs and Cardiac Resynchronization Therapy Defibrillators (CRT-D) during the year 2010 using ICD-9 codes. We then identified the patients who experienced a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
3
21
1
1
Order By: Relevance
“…in their retrospective analysis of more than 85000 patients found that higher age, congestive heart failure, coagulopathy and renal dysfunction had a higher incidence of hematoma formation after primary or de novo ICD or CRT-D implantation [3]. This is in general in line with the other published data in the literature [4], [6].…”
supporting
confidence: 72%
See 2 more Smart Citations
“…in their retrospective analysis of more than 85000 patients found that higher age, congestive heart failure, coagulopathy and renal dysfunction had a higher incidence of hematoma formation after primary or de novo ICD or CRT-D implantation [3]. This is in general in line with the other published data in the literature [4], [6].…”
supporting
confidence: 72%
“…The authors in their study also looked at the short term impact of hematoma formation and found that it increased the length of hospital stay and the cost of hospitalization [3]. Though, there was no significant increase in in-hospital mortality in their study but the actual impact on mortality can only be assessed over long-term taking into account risk of infection attributed by hematoma formation.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Bleeding in the pocket can lead to significant discomfort, increases risk of infection, and may require surgical drainage. While hematoma formation has not been associated with increased mortality it can lead to increased length of stay and costs of hospitalizations 2 .There are multiple sources from which bleeding in the pocket may occur and result in hematoma formation. These include injury to superficial veins, vascular breast tissue, insertion site vessel, and muscular arterial branches.…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of them are on antithrombotic therapy (anticoagulant, antiplatelet agents or both) 4, 5, 6. Pocket hematoma is a well recognized complication associated with CIED procedures and its risk is significantly higher when patients are on antithrombotic therapy 7, 8, 9, 10. It also increases the risk of infection in patients undergoing CIED implantations 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%